Multifaceted Determinants of Breastfeeding Practices in Udaipur, Rajasthan - Sonia; Asghar, Mohammad; Gupta, Vipin (Indian Journal of Community Health, 2024)
Background: Breastfeeding is crucial for child health and development, yet its practices and their implications on children's nutritional status vary. Aim & Objectives: This study aimed to explore the determinants of breastfeeding practices and their effects on the nutritional status of children in an Indian population. Methodology: This study is conducted in four villages of Udaipur district, Rajasthan, among 120 mother-child pairs. The data is collected on anthropometric measurements, socio-economic factors, and child health parameters. Results: We found that only 37.5% of children were exclusively breastfed. Significant associations were observed with birth month (P=<0.001) and nearly significant associations with mode of delivery (P=0.06) and undernutrition (P=0.07). Conclusion: These findings highlight the need for larger-scale research to further investigate these associations and enhance breastfeeding practices to improve child health outcomes.